2013
DOI: 10.1590/s0102-86502013000600004
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive fasciotomy in testicular torsion of the spermatic cord in rats

Abstract: PURPOSE:To evaluate the effect of decompression fasciotomy on testes undergoing torsion of the spermatic cord. METHODS:Spermatic cord torsion was induced in 40 Wistar testes for six and 12 hours. At the time of distortion, decompression fasciotomy was performed on half of the animals. After 42 days, the testicles were examined both macroscopically and microscopically.A non-parametric Mann-Whitney U-test was used for statistical analysis. The results were considered significant at p≤0.05. RESULTS:Testicular wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The effect of the tunica albuginea decompression method was primarily investigated by measuring of changes in intra-testicular pressure, testicular volume and weight and as well as with histological examination. In summary, these studies endeavored positive effect on survivability of the testis; 3 8 9 however, the results were not clearly supportive. Besides controversial results in animal models, the clinical experiences can be regarded as promising.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The effect of the tunica albuginea decompression method was primarily investigated by measuring of changes in intra-testicular pressure, testicular volume and weight and as well as with histological examination. In summary, these studies endeavored positive effect on survivability of the testis; 3 8 9 however, the results were not clearly supportive. Besides controversial results in animal models, the clinical experiences can be regarded as promising.…”
Section: Discussionmentioning
confidence: 79%
“…Quintaes et al . 9 reported larger testicular volume after 12 h torsion in DC testes compared to the DA testes. In contrast, our observations demonstrated signs of testicular atrophy on the 8 th postoperative day in both DC and DA testes presented by decreased testicular volume with even more intensive atrophy of DC testes.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…If the tunica vaginalis is considered as a tough unyielding layer, then a compartment syndrome like picture may well occur and surgical decompression may offer a chance at testicular salvage. Animal studies in rats have shown a statistically significant increase in testicular size and volume using this technique in torted rodent testicles compared with a control group [ 10 ]. Other authors have decompressed the epididymis and the spermatic cord in isolated cases with varying successes [ 7 ].…”
Section: Discussionmentioning
confidence: 99%